Way of analytical definition of magnetic forces in active magnetic bearings rotor cars - Мартыненко, Г.Ю. (Eastern-European Journal of Enterprise Technologies, 2010)
The analytical method of electromagnetic circuit analysis for active magnetic bearings (AMB) is described. The computation results for one of construction variant of axial AMB are presented. It confirms the adequacy of the mathematical description.